The Tegalsari Fishing Port Tegal Regency's Study On The Rapid Assessment Of Waste Conditions And Waste Management - Nugroho, Beni Sabdo (Jakarta Technical University of Fisheries, 2025)
Waste is a major environmental issue in PPP Tegalsari, one of the biggest fishing ports in Central Java. PPP Tegalsari is a slum, as shown by the copious amounts of trash around the port's main intersections, with a quick assessment to evaluate the PPP Tegalsari Area's waste conditions and management situation. Primary data was gathered through observation, questionnaires and waste calculation forms were used in surveys, and in-depth interviews were conducted with interview guides. On the other hand, reports from associated agencies, scientific publications, and government stakeholders were secondary data sources. The Rapid Assessment activities' outcomes from June 14–19, 2021, covered waste management, human resources, and infrastructure for waste processing.